Synthesis, crystal structure and Hirshfeld surface analysis of 5-oxo-N-phenyl-3-(thiophen-2-yl)-2,3,4,5-tetrahydro-[1,1′-biphenyl]-4-carboxamide - Khatira N. Aliyeva; Tuncer Hökelek; Victor N. Khrustalev; Rovnag M. Rzayev; Ajaya Bhattarai; Abel M. Maharramov; Namig G. Shikhaliyev (Acta Crystallographica Section E: Crystallographic Communications)
The asymmetric unit of the title compound, C23H19NO2S, contains two molecules that differ in the conformation of the two carboxamide moieties. In the crystal, intermolecular N—H...O hydrogen bonds link the molecules into chains propagating parallel to the c-axis direction. Between the molecules, weak C—H...π(ring) interactions are present, whereas π–π interactions are not observed. The Hirshfeld surface analysis of the crystal structure indicates that the most important contributions to the crystal packing are from H...H (47.6%), H...C/C...H (33.4%) and H...O/O...H (11.6%) interactions. Orientational disorder is observed for both thiophene rings.